2012
DOI: 10.1007/s10549-012-2223-1
|View full text |Cite
|
Sign up to set email alerts
|

Metformin in early breast cancer: a prospective window of opportunity neoadjuvant study

Abstract: Metformin may exert anti-cancer effects through indirect (insulin-mediated) or direct (insulin-independent) mechanisms. We report results of a neoadjuvant "window of opportunity" study of metformin in women with operable breast cancer. Newly diagnosed, untreated, non-diabetic breast cancer patients received metformin 500 mg tid after diagnostic core biopsy until definitive surgery. Clinical (weight, symptoms, and quality of life) and blood [fasting serum insulin, glucose, homeostasis model assessment (HOMA), C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
166
2
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(181 citation statements)
references
References 32 publications
9
166
2
4
Order By: Relevance
“…Overall, these prospective, preoperative window studies in breast cancer (62,64,65), despite reservations about trial design and methodology, demonstrate that metformin is safe for women with primary breast cancer and confirm the attraction of metformin as a therapeutic agent.…”
Section: Metformin and Breast Cancer Trialsmentioning
confidence: 68%
See 1 more Smart Citation
“…Overall, these prospective, preoperative window studies in breast cancer (62,64,65), despite reservations about trial design and methodology, demonstrate that metformin is safe for women with primary breast cancer and confirm the attraction of metformin as a therapeutic agent.…”
Section: Metformin and Breast Cancer Trialsmentioning
confidence: 68%
“…A second, single-center, preoperative window-of-opportunity placebo-controlled trial of similar size confirmed the reduction in Ki-67 with metformin use over 2 weeks, again not associated with BMI, and provided enhanced evidence for the systemic insulin-mediated effects (64). The need for meticulous trial design was flagged by a subsequent trial (65) where failure to continue metformin up to the time of surgery and using core samples at diagnosis versus resection specimens (66) make data interpretation difficult.…”
Section: Metformin and Breast Cancer Trialsmentioning
confidence: 81%
“…This study also provided preliminary evidence that circulating metformin level is a variable that infl uences antiproliferative activity. A third similar study ( 107 ) was smaller ( n = 39), not placebo-controlled, and also compared tissue from needle biopsies with surgical specimens. Nonsignifi cant declines in insulin level together with signifi cantly increased apoptosis and reduced proliferation were observed.…”
Section: Translational Research and Early Clinical Trialsmentioning
confidence: 99%
“…Hyperinsulinemia, insulin resistance (IR) [7,8,10], and enhanced levels of insulin-like growth factor-1 (IGF-1) [11] have all been proposed as the underlying causative mechanisms, mainly on the basis of in vitro and animal studies supporting a role for insulin, insulin receptor, and IGFs in BC initiation [12][13][14] and progression [15]. These experimental findings are strengthened by indirect observations that metformin, a biguanide oral hypoglycemic agent capable of lowering insulin levels and improving IR, also might The Oncologist 2016;21:1041-1049 www.TheOncologist.com ©AlphaMed Press 2016 be effective in reducing BC incidence [8] and may beneficially act on proliferation and apoptosis markers in early BC stages [16][17][18]. Accordingly, metformin is being investigated in an adjuvant trial investigating invasive cancer-free survival in nondiabetic women with early breast cancer (National Cancer Institute of Canada Clinical Trials Group MA.32); the primary outcome measure is expected to be released late in 2017 [19].…”
Section: Introductionmentioning
confidence: 99%